ANALISIS PENGELOLAAN ALOKASI DANA DESA DI DESA AYULA TILANGO KECAMATAN BULANGO SELATAN - Mattoasi Mattoasi; Nurharyati Panigoro; Madjid, Suryadi (Al-Buhuts, 2023)
Study This aim For know How management allocation of village funds contained in the village Come on Tilango based on applicable regulations _ Good regulation from center nor regulation from area . Study This use method qualitative with approach descriptive with use primary data sources obtained in a manner direct from observation and interview as well as outcome data documentation. The research results show that Village Come on Tilango Subdistrict South Bulango deep management finance village specifically management Allocation of Village Funds Already in accordance with what is stated in Regulation of the Minister of Home Affairs Number 20 of 2018 consisting from planning , implementation , administration , reporting , and accountability . As well as the government village Come on Tilango in implementation realization budget village fund allocation Already in accordance with Regulation Regent of Bone Bolango Number 60 of 2022 with prioritize implementation once priority .